2006
DOI: 10.1093/ndt/gfl676
|View full text |Cite
|
Sign up to set email alerts
|

The periodontal status of pre-dialysis chronic kidney disease and maintenance dialysis patients

Abstract: Periodontal disease is prevalent, severe and under recognized in renal failure patients. Prophylaxis and early dental treatment should be intensified in these subjects, and may be of interdisciplinary importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
2
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 22 publications
10
124
2
13
Order By: Relevance
“…It is difficult to interpret such situation, especially as no clear data comparing the oral condition in groups similar to our study can be found in the literature. The only similar study was our paper published 5 years ago, 38 containing the results of investigations conducted in similar groups of patients with kidney disease, and that data corresponded to the present findings. A Brazilian study of Brito et al 39 described results where, similar to our research, a worse periodontal status in HD patients compared to that in CAPD patients was found.…”
Section: Periodontal Status Of Patients With Renal Failuresupporting
confidence: 90%
“…It is difficult to interpret such situation, especially as no clear data comparing the oral condition in groups similar to our study can be found in the literature. The only similar study was our paper published 5 years ago, 38 containing the results of investigations conducted in similar groups of patients with kidney disease, and that data corresponded to the present findings. A Brazilian study of Brito et al 39 described results where, similar to our research, a worse periodontal status in HD patients compared to that in CAPD patients was found.…”
Section: Periodontal Status Of Patients With Renal Failuresupporting
confidence: 90%
“…But the exacerbation of periodontal disease, as the disease progresses from early to late stage has been reported by other investigators. A study published by Borawski et al, based on the Community Periodontal Index of Treatment Needs and described a higher prevalence of severe periodontitis among predialysis, CAPD and HD patients compared with healthy individuals (7) . In another study published by Thorman et al showed that predialysis and HD patients had significantly more clinical attachment loss than healthy subjects (20) .…”
Section: Discussionmentioning
confidence: 99%
“…This is usually associated with accumulation of bacteria with resultant tooth loss (6) . The causes for increased prevalence/severity of periodontal disease in CKD are not completely understood, but the possible mechanisms include diminished salivation and xerostomia, malnutrition, impaired immunity and wound healing, poor oral hygiene, alveolar bone destruction due to renal osteodystrophy, bleeding diathesis, and diabetes mellitus (7) . The serum level of osteocalcin and/or GCF osteocalcin in CKD patients are increased and this may also explain the effect of CKD on periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be taken into account that increased levels of uremic toxemia leads to disorders in the functioning of the immune system, which may contribute to the development of chronic inflammatory process within the periodontal tissues [24]. The outcomes of measurements that evaluate bleeding, such as Gingival Index, Sulcus Bleeding Index, or Papillary Bleeding Index may not be credible in patients with CKD, as during hemodialysis they receive anticoagulant medications, mostly heparins [25]. Even though the outcomes of research studies indicate that chronic periodontitis is observed more frequently and is characterized by a severe course in CKD patients, Craig [20] indicates that, while conducting any studies in these topics, one should take the coexistence of type 2 diabetes, smoking, duration time of dialysis, as well as demographic factors into account.…”
Section: Chronic Kidney Disease and Periodontal Statusmentioning
confidence: 99%